Answer:
y = -4x - 3
Explanation:
The slope intercept form is as follows:
y = mx + b
m = slope
b = Y-intercept
We already have the y-intercept...it is -3. This is because the y-intercept is wherever x is equal to zero. In the second pair (0,-3) we see that the x is zero so this has to be the y-intercept.
To find the slope we can use the slope equation:
Let's define the variables:
y2 = -3
y1 = 5
x2 = 0
x1 = -2
Plug them into the equation
The slope is -4
Now that we have the slope and y-intercept we can write the equation in slope intercept form:
y = -4x - 3
Hope this helps!!
- Kay :)